Evaluating the pressure generated on the container’s bottom and walls while transporting bulk cargo - Ilesaliev Daurenbek; Akhmetova Zuresh; Svetashev Aleksandr; Ismatullaev Azizbek; Shihnazarov Jamol (E3S Web of Conferences, 2023)
Now, the transportation of bulk cargo by rail is carried out with the help of specialized wagons. However, the use of such wagons leads to additional costs, there is a shortage of such wagons, as well as problems with technological equipment. In this regard, there is a need to find alternative technologies for the transportation of bulk cargo, which will reduce logistics costs and improve delivery. To solve this problem, it is necessary to start by determining the pressures that arise on the bottom and walls of the universal container when loading bulk cargo. This study shows that the problems associated with the transportation of bulk cargo can be successfully solved if the process of formation of such cargo is known. Thus, to solve the problem of bulk cargo transportation, it is necessary to develop alternative technologies that will reduce costs and improve delivery efficiency. This is possible if we study the process of forming bulk cargoes and analyze the pressures they create in containers.